Produção de nanofibras de sílica por solution blow spinning e avaliação da sua incorporação em resinas acrílicas - Santos, Gabriel Ribeiro Ferraz dos (2017)
The current concern of society for the thermal protection of homes, buildings, and industries, appealing for comfort and reduction of energy consumption has driven the research and development of materials able to withstand such requirements. Paints incorporating ceramic fibers in their composition aimed at reducing heat transfer and improving flame resistance have been an alternative to this need of modern society. Silica nanofibers was incorporated into typical acrylic resin matrices for the purpose of evaluating the thermal, mechanical, morphological, hydrophobicity and fire resistance properties. In this line, the present work was developed in two parts: (I) silicon nanofibrous production by the technique of Solution Blow Spinning from the precursor polymers PVC and PVP, followed by its characterization by SEM, TG, DSC, FTIR, XRD and BET; (Ii) production of nanocomposites through the incorporation of silica nanofibers into acrylic matrices and evaluation of thermal conductivity, specific heat, microhardness, contact angle and flame resistance. As a result, the SBS technique proved to be efficient in the production of silica nanofibers. The SEM analysis showed that the route through PVC produced fibers with better appearance and an average diameter of 113 nm. The TG and DSC analyzes showed a possible influence of TEOS on the mobility of the polymer chains. FTIR analysis indicated that the firing process completely eliminated the polymer and characteristic silica () regions were identified. DRX showed amorphous silica nanofibers and BET analysis indicated a much higher surface area for silica nanofibers produced via PVC. For the nanocomposites, the analyzes showed that the silica nanofibers had influence in the thermal conductivity and specific heat, however in an inexpressive way. The wettability of the nanocomposites did not change significantly with the incorporation of the silica nanofibers, whereas the hardness of the silica samples was increased by 15.6%, 17.1% and 17.9% for the 1, 2 and 4% samples, Respectively, as evidenced in the Vickers test. The flame resistance test showed that the nanocomposites incorporated with the nanofibers supported 14 seconds less compared to nanofiber-free resin. Thus, the behavior of nanocomposites with the incorporation of silica nanofibers was better understood.